Introduction [In Agricultural productivity in Africa: Trends, patterns, and determinants] - Benin, Samuel; Wood, Stanley; Nin-Pratt, Alejandro (International Food Policy Research Institute, 2016)
Fostering higher agricultural productivity and accelerating agricultural growth in Africa are commonly seen as core strategies for overall development in the continent (Lewis 1954; Fei and Ranis 1961; Hayami and Ruttan 1985; Hazell and Haggblade 1991; Binswanger and Townsend 2000; World Bank 2007).1 Because the majority of Africa’s poor and malnourished population depends largely on farming, these strategies can be particularly effective in reducing poverty and hunger. Yet, agricultural growth in Africa lags behind overall economic growth, and the continent’s agricultural performance has fallen further behind that of other developing regions of the world.